Advanced information systems engineering : 32nd International Conference, CAiSE 2020, Grenoble, France, June 8-12, 2020, Proceedings /: 32nd International Conference, CAiSE 2020, Grenoble, France, June 8-12, 2020, Proceedings. (2020) - Unknown
No abstract available